Exploring Ayurvedic Interventions in the Management of Atopic Dermatitis – Case Study - Nagargoje, Mahesh; Rathi, Renu; Sharma, Mahesh (Journal of Neonatal Surgery, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterized by intense itching, redness, and recurrent flare-ups. This condition arises from a combination of genetic factors, immune dysregulation, and environmental triggers, leading to a compromised skin barrier and an exaggerated immune response. Ayurvedic medicine offers a holistic approach to managing AD by focusing on balancing the three doshas—Vata, Pitta, and Kapha—and addressing the underlying toxins (Ama) that exacerbate the condition. In this case study, a 36-year-old female with chronic eczematous lesions and associated symptoms of disturbed sleep, anxiety, and constipation was treated with a combination of internal and external Ayurvedic therapies. Key treatments included Avipattikar Churna, Khadirarishta, Gandhak Rasayana, Mahatiktak Ghrita, Laghumanjishthadi Kadha, Panchatikta Ghrita Guggulu, and Raktamokshana (bloodletting). The therapeutic interventions targeted detoxification, immune modulation, and skin healing. Post-treatment, significant improvements were noted in the reduction of scaly patches, lichenification, itching, and skin discoloration. Bloodletting plays a crucial role in purifying the blood, reducing inflammation, and improving skin healing by balancing Pitta and Kapha doshas. This integrative approach, combining modern and traditional Ayurvedic therapies, offered long-term relief from AD symptoms and addressed both the physical and emotional aspects of the condition